Makna aktivitas berorganisasi bagi mahasiswa aktivis jurusan ekonomi pembangunan UM angkatan 2018 - Akbarti Na’ima; Sri Umi Mintarti Widjaja (Universitas Negeri Malang, 2021)
Abstract In addition to studying at college, students choose to participate in organizing activities to fill their free time. However, joining students in the organization has a positive impact and a negative impact. Therefore, researchers conducted a study on the Meaning of Organized Activities for Activist Students of the Department of Economic Development um Class 2018. Researchers use qualitative methods with this type of case study approach in order to know and understand individuals more deeply about what is happening in the field according to the informant's personal experience. Determination of informants using purposive sampling with the criteria of students majoring in UM Development Economics class of 2018 who follow the organization. Data collection is done by means of in-depth interviews and documentation. Then, the data is reduced, presented, and drawn conclusions. Data validity checks are conducted through source triangulation and engineering inspection techniques. From the study found several findings that the Organization followed by 3 informants namely HMJ EKP while 2 others chose to follow BEM FEB UM. Students majoring in Development Economics class of 2018 have an achievement index in the neutral category above 3.50 and experienced an increase when following the organization, but some have experienced a decrease, but not significant. The advantages of interpreting organizing activities outside of academic achievement are gaining a lot of experience, gaining relationships, mastering public speaking, starting to understand various regional languages, understanding various backgrounds of people, knowing how to work teams, feeling the external experience of the campus, as well as better knowing how to communicate with many people. Abstrak Selain belajar di perguruan tinggi, mahasiswa memilih mengikuti kegiatan berorganisasi untuk mengisi waktu luangnya. Namun, bergabungnya mahasiswa dalam organisasi memberikan dampak positif dan dampak negatif. Oleh karena itu peneliti melakukan penelitian tentang Makna Aktivitas Berorganisasi Bagi Mahasiswa Aktivis Jurusan Ekonomi Pembangunan UM Angkatan 2018. Peneliti menggunakan metode kualitatif dengan jenis pendekatan studi kasus agar dapat mengetahui dan memahami individu lebih mendalam tentang apa yang terjadi di lapangan sesuai dengan pengalaman pribadi informan. Penentuan informan menggunakan purposive sampling dengan kriteria mahasiswa jurusan Ekonomi Pembangunan UM angkatan 2018 yang mengikuti organisasi. Pengumpulan data dilakukan dengan cara wawancara mendalam dan dokumentasi. Kemudian, data direduksi, disajikan, dan ditarik kesimpulan. Pemeriksaan keabsahan data dilakukan melalui teknik pemeriksaan triangulasi sumber dan teknik. Dari penelitian ditemukan beberapa temuan yaitu Organisasi yang di ikuti oleh 3 informan yaitu HMJ EKP sementara 2 lainnya memilih mengikuti BEM FEB UM. Mahasiswa jurusan Ekonomi Pembangunan angkatan 2018 memiliki indeks prestasi dalam kategori netral di atas 3,50 dan mengalami kenaikan ketika mengikuti organisasi, namun diantaranya pernah mengalami penurunan, tetapi tidak signifikan. Keuntungan dari memaknai kegiatan berorganisasi di luar prestasi akademik yaitu mendapatkan banyak pengalaman, mendapatkan relasi, menguasai public speaking, mulai memahami berbagai macam bahasa daerah, mengerti berbagai macam latar belakang orang, mengetahui caranya kerja tim, merasakan pengalaman eksternal kampus, serta lebih mengetahui cara berkomunikasi dengan banyak orang.